Presence of Enterococcus spp. Resistant to Heavy Metals And Antimicrobials In Wild And Poultry Birds In The Province of Chubut, Argentina - Andoro, Débora Lihuen (2025)
[Introduction]: In Latin America, poor management of industrial effluents and the massive use of antibiotics in medicine and livestock farming are problems that affect human and animal health. Wild and poultry birds can act as a natural reservoir of enterococci resistant to chemicals released into the environment, contributing to their spread. [Objective]: To evaluate resistance to antimicrobials and heavy metals in enterococci isolated from wild and farmed birds in the Valle Inferior del Río Chubut region, Peninsula Valdés, Patagonia, Argentina. [Methodology]: The bacteria were isolated from 250 fresh stool samples collected from March 2019 to February 2020 and then identified by phenotypic and genotypic techniques. Resistance to heavy metals and antimicrobials was determined by the agar dilution method. [Results]: Among the 163 isolates, no resistance against cadmium and mercury was observed, while resistance was detected against nickel, copper, and zinc (99 %), chromium (98 %), and lead (95.7 %). Vancomycin and gentamicin were the most effective antimicrobials compared to the rest; only 2 strains exhibited resistance in both cases. The most frequent resistance was to ampicillin (96.9 %), followed by streptomycin (49.1 %) and tetracycline (21.5 %). [Conclusions]: Our data suggest that the presence of Enterococcus resistant to antimicrobials and heavy metals in poultry and wild birds in urban areas can become a reservoir, contributing to its spread and consequently affecting public health.